Are you emoji savvy? Exploring nonverbal communication through emojis. Issue 1 (2nd January 2020) - Yang, Yiyi
Abstract : Courses: Undergraduate courses in interpersonal communication, nonverbal communication, relational communication, computer-mediated communication (CMC), and intercultural communication, as well as basic communication courses. Objectives: The purpose of this activity is twofold: (1) to demonstrate how nonverbal communication shapes content and relational meaning in interpersonal communication; and (2) to demonstrate how nonverbal communication is rule-guided and influenced by culture.